2015
DOI: 10.1002/oby.21014
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in susceptibility to large portion sizes among obese and normal‐weight children

Abstract: Objective: Determine the association of children's susceptibility to large food portion sizes with appetite regulation and obesity. Methods: Normal-weight and obese non-Hispanic black children (n 5 100) aged 5-6 years were observed in four dinner conditions of varying portion size; portions of all foods (except milk) offered were: 100% (677 kcal), 150% (1015 kcal), 200% (1353 kcal), or 250% (1691 kcal) of those in the reference condition (100%). Condition order was randomly assigned to 2-4 children who ate tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 42 publications
1
44
3
Order By: Relevance
“…In contrast, the food responsiveness subscale consists of two items reflecting overeating (one in response to an environmental food cue and one possibly in response to the taste of food itself) and three items reflecting a general interest and desire to eat, without a reference to food cues. Although it is speculative to predict to what extent these differences in items measure differences in eating behavior, findings of one study suggest that food responsiveness is more related to overeating than to frequent cue-triggered consumption: the study reported that children with high food responsiveness consumed more energy with increasing portion sizes [36]. Future research needs to further elucidate the nuances in the underlying constructs of the external eating and food responsiveness subscale, using parental report of both subscales or child report of both subscales to eliminate confounding due to parent-child discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the food responsiveness subscale consists of two items reflecting overeating (one in response to an environmental food cue and one possibly in response to the taste of food itself) and three items reflecting a general interest and desire to eat, without a reference to food cues. Although it is speculative to predict to what extent these differences in items measure differences in eating behavior, findings of one study suggest that food responsiveness is more related to overeating than to frequent cue-triggered consumption: the study reported that children with high food responsiveness consumed more energy with increasing portion sizes [36]. Future research needs to further elucidate the nuances in the underlying constructs of the external eating and food responsiveness subscale, using parental report of both subscales or child report of both subscales to eliminate confounding due to parent-child discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous literature review was conducted and confirmed a positive relationship among obesity, diet composition, and eating behaviors [8]. One of the main factors contributing to an increase body weight is the imbalance between calorie intake, energy expenditure, and eating behaviors, including not eating at home and consuming large or excessive calories by soft drinks, snacks, and large portions [9]. Children's dietary habits have shifted away from healthy foods such as vegetables, fruits, and whole grains to fast food, processed snack foods, and carbonated soft drinks instead of water.…”
Section: Discussionmentioning
confidence: 79%
“…In school-aged children, interventions tailored to high FR girls may consist of recent innovative strategies aiming to reduce overeating in response to external food cues based on Schachter's externality theory (Schachter, 1971); (a) strategies to increase the girls' appetitive awareness by developing a greater sensitivity to hunger and satiety (Boutelle et al, 2014a); (b) strategies to strengthen self-control skills to inhibit automatic approach responses to external food cues (Appelhans et al, 2011; Verbeken et al, 2013); (c) strategies to extinguish the learned response of eating in response to external food cues (Boutelle et al, 2014a; Boutelle and Bouton, 2015); (d) strategies to train attention away from food to non-food cues (Boutelle et al, 2014b, 2016), and (e) strategies in order to adapt the food-environment, e.g., reduce portion sizes (Mooreville et al, 2015). Hence, the previous strategies aim to learn high FR children and their parents to adequately handle the children's high responsiveness to external food cues.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant moderating effect of HAS or of HAS and gender was found. It is difficult to explain these results, since the current study is to our knowledge the first to investigate this with the distal outcome “adiposity gain.” However, the assumption has already been experimentally investigated with the more proximal outcome “energy-intake” (Mooreville et al, 2015), whereby high FR children were found to be susceptible to excess energy intake when portion sizes increase. Possibly, high FR children may be more vulnerable to the amounts of food being served or to still other parameters of the home food-environment (e.g., parameters that also include drinks or foods eaten at mealtime) than to the mere availability of energy-dense snacks at home.…”
Section: Discussionmentioning
confidence: 99%